Relocation of Corporate Hazards and Poor Working Conditions in Transnational Context: Victimization in Pakistan: https://doi.org/10.5281/zenodo.17405692 - Dr. Saira Bashir Dar; Dr. Sadaqat Ali (Journal of Religion and Society, 2025)
This research paper describes the concept of contemporary issues of corporate crime with special focus on relocation of corporate hazards and poor working conditions in transnational context and its effects on people, making victimization vulnerable in Pakistan. There are different factors which become a major cause of such criminal activities of corporations in transnational context. Historically, the concept of social responsibility was very much prevalent among society men. Gradually corporations were made responsible towards society at large. With the passage of time, as man became increasingly inclined to his worldly profits, it remained more evident to find different business entities engaged in criminal activities to achieve their monetary goals even at the cost of innocent consumers and poor labour. In this dissertation, two aspects of transnational corporate crime have been described with their adverse effects on people in host developing countries. The logical conclusion of this research paper is that relocation of corporate hazards and poor working conditions cause victimization in developing countries including Pakistan which needs to be resolved by adopting strict and effective legal and regulatory measures. Keywords: Corporate crime, transnational corporations, corporate hazards, poor working conditions, developing countries, Pakistan.